Metaproteomics profiling of the microbial communities in fermentation starters (Daqu) during multi-round production of Chinese liquor - Zhao, Jinzhi; Yang, Yi; Teng, Mengjing; Zheng, Jianxujie; Wang, Bing; Mallawaarachchi, Vijini; Lin, Yu; Fang, Ziyu; Shen, Chengpin; Yu, Shaoning; Yang, Fan; Qiao, Liang; et al. (Frontiers in Nutrition, 2023)
The special flavor and fragrance of Chinese liquor are closely related to microorganisms in the fermentation starter Daqu. The changes of microbial community can affect the stability of liquor yield and quality. In this study, we used data-independent acquisition mass spectrometry for cohort study of the microbial communities of a total of 42 Daqu samples in 6 production cycles at different times of a year. The microbial composition and its changes across production cycles were revealed. Functional analysis of the differential proteins was carried out and the metabolic pathways related to the differential proteins were explored. These metabolic pathways were related to the saccharification process in liquor fermentation and the synthesis of secondary metabolites to form the unique flavor and aroma in the Chinese liquor. We expect that the metaproteome profiling of Daqu from different production cycles will serve as a guide for the control of fermentation process of Chinese liquor in the future.